The Role of Social Media Activism in Setting the Agenda of Egyptian News Sites: A Case Study of VAW Issues - El-Sherbiny, Nourhan Moustafa (International Journal of Independent Research Studies, 2025)
This study investigates the inter-media agenda-setting relationship between Instagram activism and Egyptian online news coverage of violence against women (VAW). It explores whether social media activism influences journalists’ news agendas and how they uphold professional ethics when reporting on VAW. Guided by agenda-setting, inter-media agenda-setting, and social responsibility theories, the study employs a mixed-methods design: quantitative content analysis of 418 Instagram posts and online articles from Bawbat Al-Ahram, Bawbat Al-Wafad, and Al-Watan (August 9–31, 2022), alongside in-depth interviews with five journalists. Findings reveal a limited but notable influence of Instagram activism on news agendas, particularly in stories about femicide, rape, and human trafficking. Journalists acknowledged Instagram’s role in reflecting public concern but emphasized editorial control, verification, and legal constraints as primary agenda determinants. While Instagram serves as a source of ideas, traditional gatekeeping and ethical standards still dominate content selection. The study concludes that Instagram activism enhances public awareness of VAW but remains secondary in shaping Egyptian news agendas.